Prevalence of depressive symptoms and factors associated in the elderly of the city of Pelotas-RS - Heidemann, Regiane da Silva; Vilela, Luziane Fonseca; da Cunha, Gabriela Kurz; Caldas, Renan Garcia; Salerno, Pâmela Silva Vitória; Lorenzet, Isabel Clasen; Ferrúa, Camila Perelló; de Matos, Mariana Bonati; Ghislene, Gabriele Cordenonzi; Bast, Rachel Krolow Santos Silva; Nedel, Fernanda (PAJAR - Pan-American Journal of Aging Research, 2019)
AIM: The aim of this study was to evaluate the prevalence of depressive symptoms and factors associated in the elderly of the city of Pelotas, southern Brazil. METHODS: In this cross-sectional study, the variables of interest were investigated with instruments about the socio-economic profile, aspects of physical and professional activities, eating and sleeping habits. RESULTS: 312 elderly people were interviewed, with a prevalence of depressive symptoms of 30.5%. A higher prevalence of depressive symptoms were found in women, individuals older than 81 years, from the low class, living alone, physically inactive, and retired. In the adjusted analysis, the non-practice of physical activity, low sleep quality, and daily sleeping medication were statistically associated with the outcome. In contradiction to the literature, our results refute the well-established gender roles that preconize that males are more affected by physical impairment, while the females are more affected by psychological and psychiatric disorders. CONCLUSIONS: In conclusion, it is important to identify the prevalence of depressive symptoms in a population commonly affected by other diseases. In addition, characteristics associated with depression were detected, which can help prevent or improve depression in this age group. ***Prevalencia de síntomas depresivos y factores asociados en ancianos de la ciudad de Pelotas-RS*** OBJETIVO: O objetivo deste estudo foi avaliar a prevalência de sintomas depressivos e fatores associados em idosos da cidade de Pelotas, sul do Brasil. MÉTODOS: Neste estudo transversal, as variáveis de interesse foram investigadas com instrumentos sobre perfil socioeconômico, aspectos das atividades físicas e profissionais, hábitos alimentares e de sono. RESULTADOS: Foram entrevistados 312 idosos, com prevalência de sintomas depressivos de 30,5%. Uma maior prevalência de sintomas depressivos foi encontrada em mulheres, com mais de 81 anos, de baixa classe, vivendo sozinhos, fisicamente inativos e aposentados. Na análise ajustada, a não prática de atividade física, a baixa qualidade do sono e a medicação diária para dormir foram estatisticamente associadas ao desfecho. Em contradição com a literatura, nossos resultados refutam papéis de gênero bem estabelecidos que preconizam que os homens são mais afetados pelo comprometimento físico, enquanto as mulheres são mais afetadas por distúrbios psicológicos e psiquiátricos. CONCLUSÕES: Em conclusão, é importante identificar a prevalência de sintomas depressivos em uma população comumente afetada por outras doenças. Além disso, características associadas à depressão foram detectadas, o que pode ajudar a prevenir ou melhorar a depressão nessa faixa etária. Descritores: Depressão; Saúde do idoso; Qualidade de vida.